A rare case of bilateral malignant otitis externa and osteomyelitis with lower cranial nerve sequelae. (12th May 2011) - Leahy, Travis William; Sader, Chady
Abstract : The authors present the case of a 76-year-old male who presented with right-sided recurrent malignant otitis externa (MOE) and skull-base osteomyelitis. His management involved aggressive antimicrobial therapy and multiple hyperbaric oxygen treatments. After resolution of his right-sided infection, the patient returned a short time later with symptoms and findings consistent with new, left-sided MOE with involvement of the left skull-base. With repeat treatment, the patient is now cured of his infection but poses a challenge to the treating team about future management.